Diseño e implementación de un plan de seguridad y salud en el trabajo para disminuir los riesgos laborales en la Central Térmica de Emergencia Trujillo 60 MW, APR Energy LLC sucursal del Perú, durante el 2016 - Tanaka Santillán, Fausto Eduardo (2019)
The present research deals with the design and implementation of an occupational health and safety plan for the Central Térmica de Emergencia, 60 MW APR ENERGY, branch of Peru, during 2016. Where is described the methodology for proposing a design and implementation of an occupational health and safety plan, based on the requirements of the OHSAS 18001: 2007 standard at the Central Térmica de Emergencia Trujillo, in order to comply with the safety standards for workers, protected by Peruvian laws and regulations to minimize risks and reduce the accident rate. We worked with a sample of 68 workers to make a diagnosis of the safety of the thermal power station. This serves as a starting point for the develops of a proposal for the design and implementation of an occupational safety and health plan. For the proposal of design and implementation of an occupational health and safety plan, procedures were elaborated that indicate step by step how to assign resources, functions, responsibilities, design and implementation of training, participation and consultation; document control, operational control, emergency preparedness and response; Formats were also developed which record the activities carried out to demonstrate the follow-up and traceability of the same. Where it is concluded that the design and implementation of an occupational health and safety plan for the Central Térmica de Emergencia Trujillo will allow an efficient reduction of the risks and also the accident rate